2020
DOI: 10.4018/ijmbl.2020040101
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Developmental Lens to Educational Game Designs for Preschoolers

Abstract: Preschool-aged learners process information differently from older individuals, making it critical to design digital educational games that are tailored to capitalize on young children's learning capabilities. This in-depth literature synthesis connects features of digital educational game design - including visuals, feedback, scaffolding challenge, rewards, and physical interactions to how young children learn. Preschoolers' interests and abilities (e.g., limited attention-span, early reading skills, etc.) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…By building on past research examining pre‐school learning in face‐to‐face and digital contexts, educational apps can incorporate traditional evidence‐based tactics into game design to support pre‐school learning (Callaghan & Reich, 2020). One possible way to do this is by scaffolding; that is, providing pre‐school learners with hints and support to guide them toward successfully understanding and completing educational tasks (Vygotsky, 1978).…”
Section: Guiding Early Childhood Learnersmentioning
confidence: 99%
See 2 more Smart Citations
“…By building on past research examining pre‐school learning in face‐to‐face and digital contexts, educational apps can incorporate traditional evidence‐based tactics into game design to support pre‐school learning (Callaghan & Reich, 2020). One possible way to do this is by scaffolding; that is, providing pre‐school learners with hints and support to guide them toward successfully understanding and completing educational tasks (Vygotsky, 1978).…”
Section: Guiding Early Childhood Learnersmentioning
confidence: 99%
“…The first step toward achieving this goal is understanding whether children learn from digital apps similarly to in‐person settings. Using what previous developmental and learning sciences research has identified as important for early childhood learning (eg, Callaghan & Reich, 2020; Hirsh‐Pasek et al ., 2015), this study specifically tests whether feedback and leveling features that are designed with the intent of scaffolding learning are more effective in teaching young children. The following research questions are examined:…”
Section: Guiding Early Childhood Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Edugame(educational game), very interesting to develop [10][11][12][13][14][15]. Because by playing educational games on any platform, they will indirectly learn something knowledge in the form of a game [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Edugame(educational game), very interesting to develop [10][11][12][13][14][15]. Because by playing educational games on any platform, they will indirectly learn something knowledge in the form of a game [11,13]. In this game, the game agent (intelligent agent) will give action-reaction, observe, and act on a condition so that it looks like itself.…”
Section: Introductionmentioning
confidence: 99%